The international emblem : from incunabula to the Internet : selected proceedings of the Eighth International Conference of the Society for Emblem Studies, 28th July-1st August, 2008, Winchester College /: from incunabula to the Internet : selected proceedings of the Eighth International Conference of the Society for Emblem Studies, 28th July-1st August, 2008, Winchester College. (2010) - Unknown
No abstract available